6x + 7 = 13x - 9
7 + 9 = 13x - 6x
16 = 7x
16/7 = x....or 2 2/7 = x
This is deceptively simple: there are only three terms, one is a constant (1) and two are coefficients of q (4q, -2q). To simplify the like terms, just simplify the terms containing q.
Answer: 37/66
Step-by-step explanation:
1. 148/264 = .560
2. convert to fraction 37/66
Answer:
A
Step-by-step explanation:
Both are ten numbers apart
Step-by-step explanation:
Show Solution. Start by writing the equation of the parabola in standard form. The standard form that applies to the given equation is (x−h)2=4p(y−k) ( x − h ) 2 = 4 p ( y − k ) . Thus, the axis of symmetry is parallel to the y-axis.